If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7p + 3r + (-8p) + 12r = 0 Reorder the terms: 7p + (-8p) + 3r + 12r = 0 Combine like terms: 7p + (-8p) = -1p -1p + 3r + 12r = 0 Combine like terms: 3r + 12r = 15r -1p + 15r = 0 Solving -1p + 15r = 0 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-15r' to each side of the equation. -1p + 15r + -15r = 0 + -15r Combine like terms: 15r + -15r = 0 -1p + 0 = 0 + -15r -1p = 0 + -15r Remove the zero: -1p = -15r Divide each side by '-1'. p = 15r Simplifying p = 15r
| 7-3x=(3-x)-2 | | 10x+36=6x | | 5a+3b-3a+2b= | | A-(-5)=-10 | | 15x+10-2x-12=5 | | 2y+11=27 | | x^3-7x^2+3x-21= | | -8x-2y=-4 | | 4z+5-z= | | (2x-5)+52=(5x-15) | | 7y+3(y-5)=3(y+2)-2 | | r-25=-43 | | (2x-5)+52=5x-15 | | 4n-14=-6 | | -3(6+8m)=12-9(3m+5) | | -3[s]=18 | | 6x-15+3x=7+9x-22 | | 4x+2x=15+7x | | 1260=180(n-2) | | -6n=-30 | | -9(x-8)+(17x)=8(x-3)-17 | | 8x+9y=22 | | 4b-4(1-6)=b-9 | | 12-(x+6)=7x-2 | | 3x-4=2x+12 | | 4(7x+5)= | | 3x/5+2=x | | -9+(-9)= | | Y+(-8)=6 | | 3(x-1)+45=-3x | | 9y-13-4y+9=0 | | -2(k+4)=60 |